Astrocytes in stroke-induced neurodegeneration: a timeline - Collyer, Eileen; Blanco-Suarez, Elena (Frontiers in Molecular Medicine, 2023)
Stroke is a condition characterized by sudden deprivation of blood flow to a brain region and defined by different post-injury phases, which involve various molecular and cellular cascades. At an early stage during the acute phase, fast initial cell death occurs, followed by inflammation and scarring. This is followed by a sub-acute or recovery phase when endogenous plasticity mechanisms may promote spontaneous recovery, depending on various factors that are yet to be completely understood. At later time points, stroke leads to greater neurodegeneration compared to healthy controls in both clinical and preclinical studies, this is evident during the chronic phase when recovery slows down and neurodegenerative signatures appear. Astrocytes have been studied in the context of ischemic stroke due to their role in glutamate re-uptake, as components of the neurovascular unit, as building blocks of the glial scar, and synaptic plasticity regulators. All these roles render astrocytes interesting, yet understudied players in the context of stroke-induced neurodegeneration. With this review, we provide a summary of previous research, highlight astrocytes as potential therapeutic targets, and formulate questions about the role of astrocytes in the mechanisms during the acute, sub-acute, and chronic post-stroke phases that may lead to neurorestoration or neurodegeneration.